PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN PEMERINTAH DAERAH, KAPASITAS SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADA KUALITAS LAPORAN KEUANGAN PEMERINTA DAERAH KABUPATEN ROKAN HULU (Studi Pada SKPD) - Yuli Artika; Zulbahridar '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the influence of applied the local government finance accounting system, human resources capacity and utilization of information technology to the quality of financial statements at the local government of rokan hulu regency. The population in this study are officials department, expenditures and receipts. The method that using in this study is purposive sampling method. The data of this study using primary with directly giving the questionare and analyzed using SPSS 17. The data of hypothesis were analyzed with multiple linear regression analyze approuch.The result of test hypothesis shown that the applied of the local government finance accounting system, the capacity of human resources and utilization of information technology gave the influence of the quality of financial statements at the regional government of Rokan Hulu regency. The coeficient of the determination shown that the influence of independent variables to dependent variable is 63,2% and 36,8% is affected by the other variables that not inclueded in this regression model.Keywords: Quality of Financial Statements, Local Government finance Accounting System, The Human Resources Capacity And Utilization Of Information Technology.